Module Teaching Materials in the Tissue Culture Course at the Islamic University of Riau - Fegiarti, Devi; mellisa, (Perspektif Pendidikan dan Keguruan, 2023)
This development research uses the ADDIE development model which has three stages, namely Analysis, Design, and Development. The data collection instruments used were validation sheets and validated lecturer and student response questionnaires. The sampling technique used in this research is random sampling. Data collection was carried out using validation sheets and questionnaires. The validation results by material experts show that the learning media developed get an average percentage of 89.82% (very valid). The validation results by learning media experts show that the learning media developed has an average percentage of 82.49% (quite valid). The developed teaching materials received good responses from lecturers with an average percentage of 91.31% (very good). So that from the overall assessment the average percentage of all validators is 88.85% with a very valid validity level and it can be stated that the teaching materials using the developed tissue culture module are very valid for use in learning.